Red Meat Consumption Behavior in Elazig and Consumers' Opinion in Animal Welfare - Seker, Ibrahim; Ozen, Abdullah; Guler, Hakan; Seker, Pinar; Ozden, Ibrahim (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
The current survey was undertaken to determine the consumer behavior in red meat consumption in central district of Elazig and to elaborate consumers' opinion on animal welfare. The survey was carried out in March 2010 with a total of 463 consumers. Results showed that 58.4% of the consumers preferred red meat over other meats. The species preferred ranked from the most to the least as beef (55.3%), sheep (15.3%), and goat (11.7%). As for the preparation of red meat for consumption, 40.8% of the consumers preferred barbecuing-frying, 40.8% were preparing with vegetable, 8.6% were boiling, and 9.7% were others. 44.3% of the families preferring red meat was consuming less than 4.0 kg meat/month 49.2% of the families found the meat they consume palatable. The butchers ranked first with 66.6% as the preferred place of purchase of meat. In addition, 78.8% of the consumers found the red meat they consumed as trustable. 46.0% of the consumers joined the survey thought that beef cattle were the animals facing welfare problem most. The primary problem for livestock concerned by the consumers was health services (25.0%) while the primary welfare problem that the animals were exposed to was the lack of veterinary service and care (18.0%). Parallel to these parameters, 22.0% of the consumers thought that the major problem that needs to be improved for in the life of animals were animal diseases.
Keywords: Red meat; Consumption behaviour; Animal welfare; Elazig